2020
DOI: 10.1007/s40194-020-00847-w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on the influence of the laser hybrid parameters in partial penetration welding on the solidification cracking in the weld root

Abstract: The aim of the present study is to investigate the influence of the laser hybrid welding parameters on the solidification cracks in the weld root for partial penetration welding. Welding trials were performed on thick-walled high-strength steels of grade S690QL under the same critical restraint intensity, with a variation of the welding velocity, wire feeding rate, and the focal position of the laser beam. It was ascertained that the welding velocity has a high impact on the solidification cracking phenomenon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The numerical model did not include the Marangoni effect and the surface tension, which has a great impact on the face of weld geometry. However, based on the small differences in other ( Figure 7 and Figure 8 ) weld geometries, the established model gave realistic results and was used for joint stress–strain analysis [ 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The numerical model did not include the Marangoni effect and the surface tension, which has a great impact on the face of weld geometry. However, based on the small differences in other ( Figure 7 and Figure 8 ) weld geometries, the established model gave realistic results and was used for joint stress–strain analysis [ 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heat source equation, as a basic thermal physical condition in the numerical simulation of LAHW, has received much attention from researchers. The more mature heat source models are the double ellipsoid heat source, the Gaussian heat source, and the variant heat source based on these two types of heat sources [31][32][33], in which arc heat source is usually represented by a double ellipsoid heat source or surface heat source, and laser heat sources are often represented by Gaussian heat sources. The interaction between the heat source and the material in the numerical simulation of laser-arc welding is presented by the coupling between them, and its mechanism is explained.…”
Section: Selection Of Laser and Arc Heat Sourcementioning
confidence: 99%
“…Therefore, the relative position of the laser and arc has a great influence on the multi-physical fields and deformation of welding in paraxial recombination. Bakir et al[32] found that the absolute value of laser defocusing was positively correlated with the number of weld cracks and concentrated at the root of the weld by adjusting the ratio of laser to arc heat source heat input. As shown in Figure2b, Kim et al[50] found that when arc heat input is dominant, the angular deformation is v-shaped, and when laser heat input is dominant, the angular deformation is inverted v-shaped; as shown in Figure2c, it was found by Cai et al[51] that the relative position of laser and arc can affect the velocity and direction of melt flow, and then affect the grain size and mechanical properties of the weld, the minimum grain size and the highest mechanical properties can be obtained via laser at the front of the arc region.Figure 2.…”
mentioning
confidence: 99%
“…It is assumed, that the cracks are formed mainly due to excessively rapid cooling during the last stage of solidification (where the fraction of solid metal is in the range of 0.90-0.95). Such high cooling rates provides (i) a rapid grain growth from both sides that generates a lack of fusion at the weld centerline, (ii) hard brittle phases within the area, and (iii) high tensile stresses/strains [9,40]. There are also metallurgical factors of hot cracking such as (i) the grain size and morphology within weld centerline [41]; (ii) misorientation angles of grains; (iii) segregation of harmful elements (i.e., sulfur); and (iv) the existence of the secondary phases.…”
Section: Weld Characterization Using Y-groovementioning
confidence: 99%
“…The increased hardness and high cooling rates involved in deep LBW/LAHW frequently provides cracking and porosity issues. Cracking is a common problem that mainly occurs at the weld centerline near the root area, due to the stress field during solidification [9], and is commonly referred to as solidification or hot cracking [10]. Porosity mainly forms due to unstable keyhole conditions providing poor degassing in combination with fast solidification in deep welds [11].…”
Section: Introductionmentioning
confidence: 99%